Introducing autocad 2008 - Omura, George (Wiley Pub., 2007)
Quickly master AutoCAD 2008 using this practical guide—no matter your skill level. AutoCAD author and expert George Omura presents the basics of AutoCAD 2008 and AutoCAD LT 2008 and offers clear explanations, a task-based approach, and pages of real-world examples and exercises to make this thorough book more valuable and useful than ever. Whether you’re new to AutoCAD or just looking for a quick refresher, you’ll find this focused introduction to be all you need to get quickly up to speed.